Customer Engagement and Loyalty Issues in Omnichannel Fast-Food Industry - Phang Ing @ Grace; Ng, Jing En; Fam, Kim-Shyan (Universiti Malaysia Sarawak, 2021)
Building on Social Exchange Theory and Congruity Theory, this study aims to examine the relationships between channel integration quality (i.e., channel-service configuration and integrated interaction) and congruity (i.e., self-brand image congruity and value congruity) towards customer engagement; as well as the impacts of customer engagement on customer behavioural loyalty (i.e., repurchase intention and positive WoM). Adopting convenience and snow-ball sampling methods, a total of 151 valid questionnaires were collected and analysed using SPSS 25 and SmartPLS 3.0 software. Congruity aspects play significant roles in influencing customer engagement, while channel integration qualities do not. This result could be attributed to the unique characteristics of the fast-food products and Malaysian fast-food consumers. Importantly, customer engagement influences both transactional (i.e., repurchase intention) and emotional (i.e., intention to spread positive word of mouth) loyalty positively. The findings provide useful insights to both academicians and practitioners to plan for different omnichannel strategy in the effort to increase customer engagement and desired post purchase behaviours.